A multi-national European cross-sectional study of feline calicivirus epidemiology, diversity and vaccine cross-reactivity - Afonso, Maria M.; Pinchbeck, Gina L.; Smith, Shirley L.; Daly, Janet M.; Gaskell, Rosalind M.; Dawson, Susan; Radford, Alan D. (Elsevier, 2017)
Background